An optimised spectrophotometric assay for convenient and accurate quantitation of intracellular iron from iron oxide nanoparticles. (19th May 2018) - Hedayati, Mohammad; Abubaker-Sharif, Bedri; Khattab, Mohamed; Razavi, Allen; Mohammed, Isa; Nejad, Arsalan; Wabler, Michele; Zhou, Haoming; Mihalic, Jana; Gruettner, Cordula; DeWeese, Theodore; Ivkov, Robert
Abstract: We report the development and optimisation of an assay for quantitating iron from iron oxide nanoparticles in biological matrices by using ferene-s, a chromogenic compound. The method is accurate, reliable and can be performed with basic equipment common to many laboratories making it convenient and inexpensive. The assay we have developed is suited for quantitation of iron in cell culture studies with iron oxide nanoparticles, which tend to manifest low levels of iron. The assay was validated with standard reference materials and with inductively coupled plasma-mass spectrometry (ICP-MS) to accurately measure iron concentrations ∼1 × 10 −6 g in about 1 × 10 6 cells (∼1 × 10 −12 g Fe per cell). The assay requires preparation and use of a working solution to which samples can be directly added without further processing. After overnight incubation, the absorbance can be measured with a standard UV/Vis spectrophotometer to provide iron concentration. Alternatively, for expedited processing, samples can be digested with concentrated nitric acid before addition to the working solution. Optimization studies demonstrated significant deviations accompany variable digestion times, highlighting the importance to ensure complete iron ion liberation from the nanoparticle or sample matrix to avoid underestimating iron concentration. When performed correctly, this method yields reliable iron ion concentration measurements to ∼2 × 10 −6 M (1 × 10 −7 g/ml sample).